Sociocultural Variations of Verb Markers in the West Papuan Language - Yafed Syufi; Reno Wulan Sari; Nidya Fitri; Angel Sophia Intan (CV. Creative Tugu Pena, 2023)
The problems discussed in this study are based on variations in verb meaning in west Papuan speech, namely Irires and Miyah Language. These two languages are in one area in Tambarauw Regency but have different verbs. For this reason, a study of verb and hyponymy categories is needed in morphology studies to identify variations in verb meaning in Irires and Miyah languages. This research was conducted to find out socio-cultural variations in verb meaning in the West Papuan language, namely Irires and Miyah. The researchers used qualitative, in the Iris and Miyah districts of the Tambarauw Regency. Data collection techniques were carried out by observation, interview, and documentation techniques by participating directly with the Irires and Miyah communities, supported by relevant research references as a complement to information. The instrument was an instrument in the form of a list of questions to record the classification of verb variations in prices and Miyah language. Triangulation methods carry out data analysis techniques by transcribing the results of recording variations in the pronunciation of Irires and Miyah languages which are then represented in good language and understood. The results of the study showed the use of Irires and Miyah eating verbs that resulted in verb structures that have a pronominal persona that has a practical name including d, b, a,i,u,e,o, g, ig, m, n, p, t. Keywords: Sociocultural Variation, Papuan Language, Verb Markers